Design And Analysis Of Four-point Bending Test Rig For Ladder Frame - V. Y. Raj; M. S. Yob; M. J. Ab Latif; O. Kurdi; M. S. Kassim; M. M. Izhar (Journal of Applied Science and Engineering, 2022)
This paper describes the design and analysis of a four-point bending test rig for ladder frame specimens. The test rig is used to support the specimen at two equal points when the transverse load is applied. The specimen was designed using I-beam size 100 mm X 100 mm and in the length of 6000 mm. A four-point bending experiment is performed to determine the stress and deformation towards the applied force. The existing machine to perform a four-point bending test is the Instron®5585 Universal Testing Machines (UTM). However, this machine can only measure specimen maximum up to 500 mm length. This study aims to design and fabricate a four-point bending test rig for a specimen length of 6000 mm. The testing rig design should be much stronger than the test specimen. It was demonstrated that the stress and deformation result is used to compare with the Finite element analysis (FEA) result of the specimen model. Therefore, the test rig design is analyzed to ensure that it has the capacity to withstand a maximum load that can fail the specimen. FEA was performed to determine the maximum safe load that can be applied, the safety factor, and the stresses on the test rig parts. FEA result indicates that the test rig is safe to use for the proposed specimen. The FEA results were targeted to enclose the safety factor of 1.25. An error of 1.66 % was obtained from the deformation result between both the specimen and the test rig.